2012
DOI: 10.4103/1947-2714.93376
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence and its determinants among patients on concomitant tuberculosis and antiretroviral therapy in South West Ethiopia

Abstract: Background:To benefit from therapy and to avoid contracting treatment resistant strains, the individuals must adhere to medications.Aim:The study was designed to assess the degree of drug adherence and its determinants in patients living with HIV/AIDS and TB comorbidity.Materials and Methods:A cross-sectional study was conducted to assess the degree of drug adherence and its determinants with the help of self-administered questionnaires in Tercha District Hospital in South Ethiopia.Result:A total of 24 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 14 publications
9
31
5
Order By: Relevance
“…This fining was parallel with study conducted in Ethiopian journal [31] and Debrebirhan, Ethiopia [5,31]. This study found that the patients with an initial ambulatory/ bedridden have 3 times more risk of developing treatment failure than the patients with who had working functional status.…”
Section: Sensitivity (%) Specificity (%) Ppv (%) Npv (%)supporting
confidence: 74%
See 1 more Smart Citation
“…This fining was parallel with study conducted in Ethiopian journal [31] and Debrebirhan, Ethiopia [5,31]. This study found that the patients with an initial ambulatory/ bedridden have 3 times more risk of developing treatment failure than the patients with who had working functional status.…”
Section: Sensitivity (%) Specificity (%) Ppv (%) Npv (%)supporting
confidence: 74%
“…Due to HIV's error-prone replication, high mutation rate and viral recombination, development of some HIV drug resistance (HIVDR) is inevitable, even with appropriate ART prescribing and adherence [5][6][7][8]. HIVDR has significant human and financial implications: it limits treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare provider-patient relationship was not a factor significantly associated with adherence in this study. However, the study conducted in South West Ethiopia has shown an association between healthcare provider-patient relationship and adherence [23]. Failure to find an association between healthcare provider-patient relationship and adherence in this survey could be due to the low sample size.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, the result shows that there is a good environment for caregivers and/or child patients to tell what the children felt and about their medication course for health care providers in our setting. All study participants got adequate assistance/information from health care providers in this survey like other study [23]. Health care system barriers also affect adherence, especially a regular and timely supply of medication to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a study done by Padyana et al .,[12] at a tertiary care hospital of South India, among 200 HIV positive patients, showed that 54 (27%) patients had HIV/TB co-infection and remaining 146 (73%) were HIV positive alone. Another study done by Kebede and Wabe[13] in South West Ethiopia, among 296 patients on concomitant tuberculosis and antiretroviral therapy at hospital treatment center, of them only 24 (8.1%) were co-infected by HIV and TB.…”
Section: Discussionmentioning
confidence: 99%